2020
DOI: 10.1080/15592294.2020.1748916
|View full text |Cite
|
Sign up to set email alerts
|

The DNA methylome of inflammatory bowel disease (IBD) reflects intrinsic and extrinsic factors in intestinal mucosal cells

Abstract: Abnormal DNA methylation has been described in human inflammatory conditions of the gastrointestinal tract, such as inflammatory bowel disease (IBD). As other complex diseases, IBD results from the balance between genetic predisposition and environmental exposures. As such, DNA methylation may be the consequence (and potential effector) of both, genetic susceptibility variants and/or environmental signals such as cytokine exposure. We attempted to discern between these two non-excluding possibilities by perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Interestingly, many of the publications we examined did not even mention leukocyte infiltration as a confounding factor in their quest to find disease biomarkers, despite examining inflammatory diseases [21,26,[29][30][31]. Others mentioned leukocyte infiltration as a possibility or discussed cellular heterogeneity [22,23,28,32,34] but did not control for this variability. In some cases, this occurred in meta-analyses where the authors examined previously collected data and conducting additional experimental controls was not possible [22,23,34].…”
Section: Independent Validation Of Ls-dmps In Inflammatory Diseasementioning
confidence: 98%
See 2 more Smart Citations
“…Interestingly, many of the publications we examined did not even mention leukocyte infiltration as a confounding factor in their quest to find disease biomarkers, despite examining inflammatory diseases [21,26,[29][30][31]. Others mentioned leukocyte infiltration as a possibility or discussed cellular heterogeneity [22,23,28,32,34] but did not control for this variability. In some cases, this occurred in meta-analyses where the authors examined previously collected data and conducting additional experimental controls was not possible [22,23,34].…”
Section: Independent Validation Of Ls-dmps In Inflammatory Diseasementioning
confidence: 98%
“…cn/ ewas/ atlas) [20], we discovered 28 associated traits from 35 publications (Table S2) that were associated with our ls-DMPs. The top three traits with the highest number overlapping CpG sites were psoriasis (33 DMPs identified by Chandra et al [21]), inflammatory bowel disease (IBD) (12 DMPs identified by Agliata et al [22]), and Alzheimer disease (AD) (12 DMPs identified over three publications [23][24][25]).…”
Section: Independent Validation Of Ls-dmps In Inflammatory Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…IBD consist of multifactorial diseases, whose pathophysiological architecture is based on predisposing genetic factors added to environmental factors and the intestinal microbiota, as illustrated in (Figure 2). However, studies still seek to elucidate better these elements and how they participate in the development of an exacerbated and extremely harmful inflammatory response [22][23][24].…”
Section: Inflammatory Bowel Disease: Pathophysiologymentioning
confidence: 99%
“…DNA methylation (DNAm) is one of the main epigenetic mechanisms known to play a key role in regulating cellular function of human cells including the intestinal epithelium 7,8,[15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%